(untitled) (Konturen, 2015)
Both Søren Kierkegaard and Friedrich Nietzsche maintained an abiding concern for Socrates throughout their productive lives. Kierkegaard wrote his dissertation on irony through a Socratic lens and Nietzsche once declared that try as he might, he could not completely separate his concerns from those he associated with the Greek. Kierkegaard famously favored Aristophanes’ portrait of Socrates in his comedy Clouds, claiming that it accurately portrayed the illegibility of the ironist. Nietzsche leaned toward Xenophon’s Socratic writings but most famously blamed Plato’s Socrates for the demise of tragic culture. Kierkegaard and Nietzsche engaged with the variety of Socratic depictions throughout their careers and perhaps more importantly, both employed irony in a Socratic fashion inflected by textual concerns. In other words, Kierkegaard and Nietzsche understood irony as both the indication of an epistemological limit, and as a strategy to induce the reader to think herself into the text. My article “Clouds: The Tyranny of Irony over Philosophy” analyzes this common concern and its implications for our understanding of European modernity.